THE PERFORMANCE ANALYSIS OF REACTIVE AND PROACTIVE ROUTING PROTOCOLS FOR V2V COMMUNICATION IN DYNAMIC TRAFFIC SIMULATION - Bintoro, Ketut Bayu Yogha; Syahputra, Ade; Rismanto, Akmal Hadi; Marchenko, Michael (Informatika, Universitas Jenderal Soedirman, 2024)
The research problem addressed in this study arises from the urgent need to enhance Vehicle-to-Vehicle (V2V) communication in dynamic traffic scenarios. V2V communication is a critical component of intelligent transportation systems aimed at improving traffic safety and efficiency. However, existing routing protocols exhibit varying performance under different traffic conditions, such as free flow, steady flow, and congestion. Consequently, a comprehensive comparison is necessary to evaluate the effectiveness of three routing protocols—AODV, LA-AODV, and DSDV—in dynamic V2V scenarios. This research aims to address this problem by simulating realistic traffic conditions and evaluating the Quality of Service (QoS) of each protocol using metrics such as Packet Delivery Ratio (PDR), Packet Loss Ratio (PLR), Throughput, End-to-End Delay, and Jitter. The findings indicate that LA-AODV demonstrates superior performance in terms of PDR (up to 4% at 500 seconds), PLR (reaching 95.33% at 500 seconds), and Throughput (reaching 84.81 Kbps at 800 seconds). This makes it an excellent choice for applications prioritizing reliable data transfer. Conversely, AODV exhibits the lowest latency and jitter, with latency (reaching 7.40E+10 ns) and jitter (reaching 1E+10 ns) at 300 and 400 seconds, respectively. AODV is well-suited for real-time V2V communication due to its minimal delay and jitter. DSDV, while minimizing control overhead, performs less favorably in other metrics. Consequently, AODV emerges as the preferred option for real-time V2V communication. LA-AODV excels in scenarios emphasizing data delivery and high throughput. DSDV may find relevance in security-sensitive applications where minimizing control traffic is crucial.